American Jewish humor - Caplan, Jennifer (Religion compass, 2022)
This article charts the development of the particular genre generally known as “Jewish humor.” It provides and overview of the topic for those interested in the relationship between American Jews and humor and the phenomenon of Jewish humor. It aligns the history of the genre with the history of Jews in America to demonstrate the ways in which changes in Jewish American social status was reflected in the type of humor being produced, as well as the way that the evolution of popular media platforms were often shaped and dominated by Jewish content producers. It begins with Yiddish film and theatre and continues through radio and early television, stand-up comedy, the late twentieth century boom in Jewish sitcoms, the rise of “Generation Hanukkah Song,” and finally the current move toward Internet and social media humor.